EVOLUTION OF LOCAL ELECTRONIC STRUCTURE IN ALABANDITE AND NININGERITE SOLID SOLUTIONS [(MN,FE)S, (MG,MN)S, (MG,FE)S] USING SULFUR K- AND L-EDGE XANES SPECTROSCOPY - Farrell S.P.; Fleet M.E.; Stekhin I.E.; Kravtsova A.; Soldatov A.V.; Liu X. (My University, 2002)
Synchrotron radiation S K- and L-edge X-ray absorption near-edge structure (XANES) spectra are reported for the cubic, rocksalt (B1) structure sulfides niningerite (MgS), alabandite (MnS), and oldhamite (CaS), and for their solid solutions (Mn,Fe)S and (Mg,Mn)S, and S L-edge XANES spectra are reported also for (Mg,Fe)S solid solutions. Pre-edge features at the S K-edge are attributed to transition of S 1s electrons to the lowest available unoccupied S 3pσ* antibonding states hybridized with metal 3d(eg) states, and at the S L-edge to transition of S 2p electrons to unoccupied S 3sσ*, 4s σ*, and 3d antibonding states hybridized with metal 3d(eg) states, and to a lesser extent 3d(t2g) states. The S K-edge XANES spectra for the solid solutions show a progressive participation of 3d orbitals in metal-S bonding with increase in substitution by Fe in (Mn,Fe)S and (Mg,Fe)S and Mn in (Mg,Mn)S through progressive increase in the area of the pre-edge feature. However, the pre-peak area does not increase linearly in each solid solution series showing that a real change in bulk electronic properties has occurred. Increase in pre-peak area reflects an increase in overall attainability of metal 3d states for hybridization with S 3pσ* antibonding states as proportionally more metal 3d orbitals become available. The S L-edge XANES spectra show progressive evolution of pre-edge features at the L3- and L2- edges (a1 and a2, respectively). Only a2 is present in the S L-edge XANES spectrum of FeS (troilite), and with progressive decrease in Fe content in (Mn,Fe)S and (Mg,Fe)S solid solutions, a1 first appears, then becomes dominant. Since a1 is attributed to transition of S 2p3/2 electrons to S 3sσ* states hybridized with metal 3d(eg) and 3d(t2g) states, this appears to represent an increased contribution from metal-S π-bonding. The results show that the size and position of the pre-edge features to the S K- and L-edges are controlled more by the DOS of hybridized 3d(egβ) and 3d(t2gβ) states and nearest-neighbor coordination of the metal atoms than by the precise coordination of S and the extended structure of the sulfide. The full multiple scattering approach has been applied to the calculation of the S K-edge XANES spectra of MgS, MnS, and CaS. Results are consistent with experimental XANES spectra, especially for the pre-edge features, which are often neglected in such calculations.